TNF-alpha Inhibitors Induced Eosinophilia: A Case Report of an Undervalued Side Effect of Such Biologicals - Diomeda, Federico; Calogiuri, Gianfranco; Congedo, Maurizio; Filoni, Angela; Sordi, Emiliano; Fiore, Massimo; Pietroleonardo, Lucia; Piscitelli, Prisco; Civino, Adele (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
IntroductionWe present an unusual case of a 28-year-old rheumatologic male patient who developed eosinophilia while he was on etanercept therapy previously and then on golimumab.Case RepresentationAlthough eosinophilia is rarely reported in the literature as a side-effect of various Tumor Necrosis Factor-alpha (TNF-alpha) antagonists, it represents a riddle about the future treatments of these patients since the persistence of therapy might lead to the onset of dermatologic or visceral eosinophilic complications in such patients.ConclusionFurthermore, the pathogenesis of eosinophilia is still unknown, and all the proposed hypotheses do not explain the eosinophilic proliferation in certain subjects.
Keywords: etanercept